FLIPPED CLASSROOM LEARNING TOOLS TO MAXIMIZE ABILITY THINKING HIGH LEVEL OF STUDENTS - Hamzah Upu; Andi Ika Prasasti Akbar (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to produce a flipped classroom device that utilizes google classroom to optimize high-order thinking skills of high-quality students. This type of research is Research and Development. The development model used is the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This research was conducted in Mathematics Education class 1.2 semester 3, Faculty of Tarbiyah and Teacher Training at UIN Alauddin Makassar. The research instrument used expert validation sheets, student and lecturer response questionnaires, and learning outcomes tests. The results showed that the average score of the validation results of learning tools: Lesson Plans, Learning Videos, Online Assignments and Higher Order Thinking Ability Tests were valid based on the criteria assessment. the practicality of learning tools based on positive student and lecturer responses. The effectiveness of the learning device is seen from the completeness of the higher order thinking ability test results that have been achieved. Through the development phases, quality products are produced that meet the criteria of validity, practicality and effectiveness